Functioning of the Russian Language in Transborder Territories of the Arctic Region (As Exemplified by Northern Norway) - Nikolaevna Ivanishcheva, Olga; Vyacheslavovna Koreneva, Anastasiya; Vitalevna Ryzkova, Inna; Vyacheslavovna Burtseva, Alexandra; Anatolievna Rotaryanu, Lubov (International Journal of Engineering and Technology, 2018)
The research relevance is explained by the need to determine trends and prospects for the historical and cultural development of the Arctic Region with due regard to its multicultural evolution and existence forms, as well as by the importance of addressing the burning issue of the functioning of a national language in the context of globalization. The article aims to identify common trends in the functioning of the Russian language in transborder territories of the Arctic Region (the border area between the Murmansk Region and Northern Norway). The research novelty is in revealing the situation around minority languages of the Russian expat community living in Northern Norway. The article demonstrates that the Russian language is used in everyday communication, advertisements, announcements and signboards in the transborder region of Northern Norway by locals and a large number of Russian tourists but it has not become dominant among the population of the city of Kirkenes. At the same time, the linguistic isolation of Russian-speaking and Norwegian-speaking groups is obvious and is characterized by certain asymmetry like the relationship between Norway and Russia as a whole.Â